EDITORS’ NOTES - Lachman, Magdalena; Ojrzyńska, Katarzyna (Prace Polonistyczne, 2020)
The texts that we present in this issue of “Studies in Polish Literature” have been collected under the title: “Deficit in Polish Literature and Literary Studies – Analyses and (Re)Visions”. Writing the call for articles, we decided that what serves as an advantage of the term ‘deficit’ is its semantic indeterminacy, the fact that it balances on the verge of many nuanced and accumulated meanings, engages with a number of problems, and can be applied in many contexts, even if sometimes it lacks terminological precision or clarity. We have used the concept of a ‘deficit’ not so much as an axiological, but more as a descriptive category with the aim of unlocking the cognitive potential of the term and encouraging a reflection, both general and particular, on Polish literature and literary studies. To facilitate this task, we have listed a number of key topics and issues which we invited our contributors to tackle and which, as it has turned out, often overlap and cannot be easily separated. As the articles that we have gathered show, the question of deficit can be addressed in many creative ways, even if the conceptual framework of the journal issue was not strictly defined, but only broadly sketched. The articles study various aspects of deficit, lack, absence, and scantiness. Some of them identify various shortages, white spots, and forms of silence that are conspicuous in Polish literature and literary studies, using different confrontational, comparative, or prescriptive perspectives. They explore methodological and thematic deficits and investigate the ways in which they can be and have been reduced and eliminated. Adam Regiewicz, for instance, ponders on the possibility of adapting porn studies to the Polish context, while Arkadiusz Morawiec explores the so far under-researched motif of Unit 731 (a secret research unit of the Imperial Japanese Army that implemented the programme of the development and production of chemical and biological weapons that was initiated in the 1930s by general Shirō Ishii) in Polish literature and seeks to answer the question of why the surprisingly numerous literary allusions to Unit 731 do not provoke much reflection on history, collective memory, or ethics, and if this can be changed. Other issues that our contributors have tackled include, on the one hand, deficits and fluctuations in the international reception of Polish literature (Jan Jeništa examines the reasons why Polish most contemporary, 21st-century literature, and particularly experimental literary works, have not received much public notice in the Czech Republic, in spite of the institutional support and the translation boom in Poland), and, on the other hand, adaptation problems, i.e. the poor assimilation of certain perspectives and terminologies used in foreign literary studies (Beata Śniecikowska analyses the Polish reception of English and American imagism as well as the interrelated terminological and interpretative issues that remain a problem till this day). In this context, it is also crucial to investigate whether a given ‘deficit’ is actually indicative of an objective and indisputable absence or rather results from perceptual failure, neglect, marginalization, distortion, obfuscation, one’s cognitive stereotypes or inability to decode the hidden meanings, or/and the impact of authoritarian statements made by writers or of canonical interpretations of their works. These issues are discussed in a comprehensive manner by Monika Bednarczuk, whose article studies regional women’s writing in the interwar period through the lens of new regionalism, gender studies, ecofeminism, and ecocriticism. Our contributors did not solely focus on that which seems to be missing from Polish literature and literary studies (problems, questions, conventions, motifs, methodologies, trends in literary reception, and research questions). They have also examined how Polish literary studies can make an important and original contribution to the humanities (Joanna Matyjaszczyk points to the way in which Polish studies of religious poetry could be adapted to the Anglo-Saxon context). Apart from searching for problems and topics that have so far been evidently overlooked and neglected, the present issue of “Studies in Polish Literature” focuses on the areas that have not been investigated thoroughly enough and those that only seem overexploited and thus may be difficult to re-examine in a creative manner. This issue is addressed in Kasper Pfeifer’s article, which reflects on Polish Futurism and its accelerationist and emancipatory dimensions that aimed to modernize the interwar Polish society, and a separate section of texts on Julian Tuwim, who still enjoys considerable popularity among Polish readers. The popularity has not, however, encouraged many reinterpretations of his oeuvre through contemporary lens. This begs a question about the effects that the year 2013, which was proclaimed the Year of Julian Tuwim, has had on popularizing the works the author of the immortal Lokomotywa (The Locomotive) and the rebellious Absztyfikanci Grubej Berty (Big Bertha’s Suitors) and stimulating readers’ interest. When viewed from yet another perspective, deficit may be seen as an intrinsic element of a given work. It may be a theme or part of the world depicted in the text, of the worldview that it communicates, or of the emotional lives of the characters. A deficit may as well serve as a formal device consciously applied by a writer. It can also be an effect of various tensions between literary works and the social contexts in which they function, their genesis, and the motivation behind the artistic choices made by an author. Approaching Anna Wiśniewska-Grabarczyk’s critically-acclaimed Porzeczkowy Josef (Currant Josef) from this perspective, Marzena Woźniak-Łabieniec analyzes emotional deficits as a literary theme in the novel. Last but not least, the articles collected in this issue offer a reflection on deficit understood as an analytical category that is closely connected with the idea of the ‘norm’ and the criticism thereof. Defined as a social and cultural construct, deficit is a crucial concept in critical minority studies. It plays an important role in contemporary disability studies, ethnic and race studies, gender and queer studies, and the studies of the intersectionality of various forms of discrimination. In these contexts, the characteristic features of the Other (defined through the prism of disability, gender, sexual orientation, race, ethnicity, wealth, class affiliation, or religion) are often perceived in terms of lack and/or deviation. This perspective offers a space for the investigation of the ways in which various literary representations either reinforce the above-mentioned biased approaches or question and verify them, in a subversive fashion challenging the existing hierarchies and depicting the alleged ‘deficit’ as a feature that is valued and desired. The issue of how the so-defined deficit as well as the absence of certain voices in the public sphere are addressed in Polish disability life writing is discussed in Katarzyna Ojrzyńska’s and Klaudia Muca’s articles. The former analyses how Maria Reimann’s 2019 autoethnographic novel problematizes some key concepts for contemporary disability studies, including deficit and lack, while the latter explores the potential for expanding the so far limited paradigm of interpreting disability narratives, which is typical of medical humanities, by taking recourse to literary studies. All of the above-mentioned issues find a reflection in the texts presented below, but do not exhaust the topic. ‘Deficitology’ encompasses a much broader list of problems that call for further research. When viewed from a historical perspective, deficit and scantiness may, for instance, be seen as markers of artistic transformations or changes in trends in literary reception. Some other areas of interest include: the shortage of rhymes in poetry, the deficit of epic poetry, the deficit of fiction that offers a panoramic view of society, the deficit of beauty, the deficit of ornamentation, the deficit of pathos, the deficit of seriousness, and the deficit of intellectually stimulating content… Deficitologists could also address the diminishing and disappearing scholarly interest in works of the writers who once enjoyed high popularity and attracted considerable critical attention (such as Konstanty Ildefons Gałczyński or Edward Stachura). The key question here concerns the possible reasons for such ‘deficits’ (e.g. the role of fashion in shaping popular interest in various literary phenomena, the influence of different cultural restrictions and changes, artistic transformations, or/and other factors that determine scholarly and popular interest). This prompts us, for instance, to reflect on the future of versification studies, on how Bolesław Leśmian studies has been saved from falling into oblivion, and on whether such an impasse is more of a threat to a scholar researching Adam Mickiewicz’s oeuvre or the one who studies the works by Dorota Masłowska, Władysław Reymont’s novels, or Witold Gombrowicz’s works, a scholar of prosody or one that specializes in visual poetry, an aficionado of deconstruction or an editor and genologist, etc. Furthermore, some thought should be given to the way in which the discourse of Polish literary studies, and its methodologies related to the variously defined concept of deficit have evolved over time. Such a perspective may help answer the question not only about the possible deficits in Polish literature and/ or literary studies, but also about the extent to which a given deficit results from adopting a specific, hierarchical perspective, the extent to which it is painful and problematic, and the extent to which it is specific to the Polish context. It may also help determine whether Polish literary studies has made (or are making) any important, original contribution to the humanities, in general. In other words, the thematic scope of the issue opens new pathways for examining the innovativeness of Polish literary studies as well as for commenting on the ways in which Polish scholars may develop their important and original perspectives on the issues that are specific to the Polish context. Deficit can easily be seen as related to the limited productivity of certain ideas, which particularly rings true in the times when the rapid increase in the number of analytical works does not automatically improve the quality of research or facilitate progress. Thus, another question that begs to be asked concerns the reasons why given methodologies, even if effective in other temporal and cultural contexts, do not bring the expected results in different configurations. This brings us to the question of whether theories and methodologies that have been developed elsewhere can easily be translated into the Polish context. Do they need any modifications? Or, perhaps, do they turn out to be partly or totally incompatible with Polish literature and the specificity of Polish literary studies? Having discussed only the major aspects of the above-mentioned research questions, we hope that the present issue of “Studies in Polish Literature” will diagnose various problems and fill in some blank spaces in Polish literary studies. We hope that it will show when a deficit poses danger, when it is a problem that needs to be named and examined, when it contributes to the development of various genres, formal devices, concepts, and worldviews, and when it is not so much an obstacle, but a driving force stimulating progress. Finally, we hope that this ‘deficit-oriented’ collection of articles will compensate for the deficits in various areas as well as whet the reader’s appetite for more – i.e. we hope that these texts will encourage reflection on and further creative examination of the issues that have been addressed or only briefly mentioned here and that they will not only garner applause, but also spark constructive, critical debates. In other words, we hope that this journal issue will appeal to many readers and stimulate academic research and interest in deficit. Deficit, after all, may effectively generate an appetite for knowledge.